Customer-supplier relationship management performance model for SMEs: missing link between logistic and business intermediaries / Muhamad Fairos Mohamad Shah, Samsudin Wahab and Mohd Subri Tahir. - Mohamad Shah, Muhamad Fairos; Wahab, Samsudin; Tahir, Mohd Subri (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
Small and medium enterprises (SMEs) are playing an increasingly important role in sustaining economic growth and logistic system in Malaysia. SMEs also play a very crucial role in customer relationship as they may serve the roles of customer, distributor producer and supplier. However, the adaptation of customer relationship in Malaysian SMEs has not been broadly explored. C-SRMP model for logistic service presents the combination of financial strategy, location strategy, business process strategy, and technology strategy. Further study has important managerial implications as the findings will enable management of SMEs to understand progressive and highly varied C-SRMP practices and contextual factors that contribute to the SRMP as well as effective, efficient and innovative implementation.